Property-oriented Production of Forged Magnesium Components. (2015) - Graf, M.; Ullmann, M.; Kawalla, R.
Abstract: The significance of light-weight construction in the automotive industry continues to increase. The reasons for this lie, for example, in the reduction of CO2 emissions achieved by fuel savings due to reductions in automobile weight. Low vehicle weights can be achieved through material substitution or improved topologies. Steel, however, remains the most commonly used material for the manufacture of forged components in the automotive industry. The use of drop-forged aluminium components has clear advantages in terms of vehicle mass. However, the use of magnesium components would result in even greater savings (magnesium is 25 % lighter than aluminium). Although magnesium is the lightest metallic structural material and, therefore, the theoretical potential for application is huge, research into the material is in its infancy. The scepticism with respect to magnesium as a structural material arises from preconceptions regarding its flammability, as well as the problem of its susceptibility to corrosion – which to date has not been solved satisfactorily. In addition to process design and the evaluation of the forgeability of the material, the material-specific variables as well as the specific tensile strength and notched-bar impact value were determined using a demonstration component. In addition, process- and material-dependent microstructural characterisations were carried out. To determine the material flow, the temperature distribution, and the degree of deformation, a numerical simulation was applied. This paper shall demonstrate the potential of magnesium using as an example the magnesium alloy AZ31, in order to establish this material in the future as one that is suitable for forging. Ultimately, the results obtained speak strongly for the use of magnesium alloys as forging materials.